Digital terrestrial television measurement and coverage models comparison: Evaluation of measurements and simulations on urban enviroment for DVB-T2 signals (2016)
This paper presents the measurement process of DVB-T2 signal in an urban environment, and the simulations with a coverage calculation tool able to configure specific details of digital television signals and a detailed cartography. Empirical and simulations results are compared to determine additional settings and correction factors. Additional considerations to support signal planning processes are presented.